Persepsi Siswa Terhadap Pembelajaran Online Pada Masa Pandemic Covid-19 Di Sekolah Dasar Negeri 4 Kota Banda Aceh - Cut Ratna Kemalasari; soedirman Soedirman; Mislinawati Mislinawati (Universitas Syiah Kuala, 2023)
Student perception is the point of view and understanding of students on the material or information received by students when learning activities take place. The formulation of the problem in this study is how students perceive online learning during the covid-19 pandemic at State Elementary School 4 Banda Aceh City. This study expects to describe students' opinions on online learning during the COVID-19 pandemic at State Elementary School 4 Banda Aceh. The approach used in this study is a qualitative, descriptive type of research. This research was conducted at the State Elementary School 4 Banda Aceh. The subjects in this study were students in grades 4a and 5a, totaling 64 students as well as teachers or homeroom teachers of grades 4a and 5a and 5 other teachers. Data collection techniques using questionnaires, interviews and documentation. Data analysis techniques through data reduction, data presentation and drawing conclusions. Based on the results of research on students through the questionnaire method, many students do not like online learning because they do not understand the material presented by the teacher and feel more comfortable with face-to-face learning. Likewise, according to the results of interviews with teachers, online learning is considered inefficient due to several obstacles including many students and parents of students who do not have gadgets (HP) so that teachers find it difficult to deliver learning materials. The results of the research of students and teachers of State Elementary School 4 Banda Aceh City showed students' perceptions of online learning during the Covid-19 pandemic at State Elementary School 4 Banda Aceh City in the 2020/2021 academic year in the good category with an overall percentage of 68%.